Trophoblast cell differentiation in the bovine placenta: differentially expressed genes between uninucleate trophoblast cells and trophoblast giant cells are involved in the composition and remodeling of the extracellular matrix and O-glycan biosynthesis - Polei, Marina (BMC Mol Cell Biol, 2020)
BACKGROUND: In the bovine placenta, intimate fetomaternal contacts are restricted to discrete placentomes. Here, widely branched fetal chorionic villi interdigitate with corresponding maternal caruncular crypts. The fetal trophoblast epithelium covering the chorionic villi consists of approximately 80% uninucleate trophoblast cells (UTCs) and 20% binuclear trophoblast giant cells (TGCs). The weakly invasive TGCs migrate toward the caruncle epithelium and eventually fuse with individual epithelial cells to form short-lived fetomaternal hybrid cells. In this way, molecules of fetal origin are transported across the placental barrier and released into the maternal compartment. The UTC/TGC ratio in the trophoblast remains almost constant because approximately as many new TGCs are produced from UTCs as are consumed by the fusions. The process of developing TGCs from UTCs was insufficiently understood. Therefore, we aimed to detect differentially expressed genes (DEGs) between UTCs and TGCs and identify molecular functions and biological processes regulated by DEGs. RESULTS: We analyzed gene expression patterns in virtually pure UTC and TGC isolates using gene arrays and detected 3193 DEGs (p < 0.05; fold change values < − 1.5 or > 1.5). Of these DEGs, 1711 (53.6%) were upregulated in TGCs and 1482 (46.4%) downregulated. Gene Ontology (GO) analyses revealed that molecular functions and biological processes regulated by DEGs are related to the extracellular matrix (ECM) and its interactions with cellular receptors, cell migration and signal transduction. Furthermore, there was some evidence that O-glycan biosynthesis in TGCs may produce sialylated short-chain O-glycans (Tn antigen, core 1 O-glycans), while the synthesis of other O-glycan core structures required for the formation of complex (i.e., branched and long-chain) O-glycans appears to be decreased in TGCs. CONCLUSION: The differentiation of UTCs into TGCs particularly regulates genes that enable trophoblast cells to interact with their environment. Significant differences between UTCs and TGCs in ECM composition indicate reduced anchoring of TGCs in the surrounding matrix, which might contribute to their migration and their weakly invasive interaction with the maternal endometrium. Furthermore, increased expression of sialylated short chain O-glycans by TGCs could facilitate the modulation of maternal immune tolerance.